Getting drones off the ground in Africa - Mbuya, Frederick E.; Rambaldi, Giacomo; Chaham, Hamza R. (Technical Centre for Agricultural and Rural Cooperation, 2017)
Unmanned aerial vehicles (UAVs), popularly known as drones, have flown out of the pages of science fiction and arrived in Africa. A rush of recent research, pilot and exploratory activities have evaluated the technology and identified sectors where it can best benefit the people of the continent. Now it is questions of national policy that will determine how far drones will go